Elimination of Quadratic Phase Aberration in Digital Holographic Microscopy by Using Transport of Intensity - Zhou, Wenjing; Liu, Shili; Wang, Chen; Zhang, Hongbo; Yu, Yingjie; Poon, Ting-Chung (Frontiers in Photonics, 2022)
We propose to reconstruct 3D images by combining the merits of transport of intensity and digital holography. The proposed method solves the transport-of-intensity equation by using digital holographic reconstructed images as inputs. Our simulation and experimental results show that this method can eliminate the quadratic phase term introduced by the microscope objective in digital holographic microscopy. This proposed phase retrieval method is free of phase unwrapping process. It is thus efficient in removing the quadratic phase term introduced by the microscope objective.